Addressing Racial Disparities in Live Donor Kidney Transplantation Through Education and Advocacy Training. Issue 9 (September 2020) - King, Elizabeth A.; Ruck, Jessica M.; Garonzik-Wang, Jacqueline; Bowring, Mary G.; Kumar, Komal; Purnell, Tanjala; Cameron, Andrew; Segev, Dorry L.
Abstract : Background: The Live Donor Champion (LDC) program trains kidney transplant (KT) candidates and their family/friends ("champions") as educator-advocates for live donor KT (LDKT). This program was created to empower patients and champions, particularly African American (AA) waitlist candidates that historically had lower access to LDKT. We assessed changes in knowledge about and comfort discussing live donation and donor referral associated with LDC participation, both overall and by participant race. Methods: We compared 163 adult KT candidates who were LDC participants from October 2013 to May 2016 with 489 matched controls, both overall and by race. We compared changes in comfort and knowledge post-LDC using rank-sum tests among participants by race. We compared time to first live donor referral for participants versus controls, by race, using Cox regression. Results: Post-LDC versus pre-LDC, participants had higher median knowledge (83% versus 63% on 12-question quiz; P  < 0.001) and comfort (1.8 versus 1 on 4-point Likert scale; P  < 0.001). Among participants, AAs had similar baseline and final knowledge ( P  = 0.9 and P  = 0.1, respectively) and baseline comfort ( P  > 0.9) as non-AAs but higher final comfort (2 versus 1.4; P  = 0.005) than non-AAs. LDC participants were 5.8 times as likely as controls to have a live donor referral (aHR 3.76 5.788.89 ; P  < 0.001); the impact of LDC participation was similar among non-AAs and AAs (p-interaction = 0.6). Conclusions: The LDC program increased knowledge, comfort, and live donor referral for non-AA and AA participants, underscoring the effectiveness in the program in promoting LDKT in a population with historically lower access to LDKT.